Behaviour of reinforced concrete beams without stirrups subjected to steel reinforcement corrosion - Azam, Rizwan; El-Sayed, Ahmed K.; Soudki, Khaled (Journal of Civil Engineering and Management, 2016)
The effect of corrosion on the structural behaviour of reinforced concrete (RC) beams without stirrups was experimentally investigated. A total of seven medium-scale RC beams without stirrups were constructed. The beams measured 150 mm wide, 250 mm deep and 1700 mm long. The test variables included: three different longitudinal reinforcement ratios (0.91%, 1.21%, and 1.82%) and two different corrosion levels (3% and 10%). Four beams were subjected to artificial corrosion whereas three beams acted as control un-corroded. Following the corrosion phase, all beams were tested to failure in three point bending. Corrosion crack widths and cracking patterns were recorded at different stages of corrosion. The effect of different longitudinal reinforcement ratios on the rate of corrosion was observed. Test results revealed that the beams with higher reinforcement ratios experienced slower corrosion rate compared to beams with lower reinforcement ratios. All control beams failed in shear whereas corroded beams failed in bond. There was a significant reduction in the load carrying capacity of the corroded beams without stirrups compared to the control beams.